Proccedings of the ICAIIT2016 2016
DOI: 10.20544/aiit2016.i01
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Approaches in Software Process Assessment

Abstract: Abstract. Software processes play important role in overall business performances of software organizations. However, in many cases processes are not well established, leading to poor performances of software products and services. Since majority of software organizations are small, suffering from the lack of resources, there is a permanent need for developing lightweight inductive approaches for assessing and improving their processes. These approaches should start from the actual state of the practice in sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…This research is used the triangulation method that can assist in confirming the set of findings based on the hypothesis (Noble & Heale, 2019). The triangulation data is collected using the mixing method to ensure in-depth set of findings, including both, quantitative and qualitative data sources, data triangulation assumed by using various sources of data within an organization (Stojanov, 2016). To collect the quantitative data, it is usually obtain from an available document from an organisation.…”
Section: Methodsmentioning
confidence: 99%
“…This research is used the triangulation method that can assist in confirming the set of findings based on the hypothesis (Noble & Heale, 2019). The triangulation data is collected using the mixing method to ensure in-depth set of findings, including both, quantitative and qualitative data sources, data triangulation assumed by using various sources of data within an organization (Stojanov, 2016). To collect the quantitative data, it is usually obtain from an available document from an organisation.…”
Section: Methodsmentioning
confidence: 99%
“…Literature review related to software process assessment revealed that lightweight process assessment methods, which are designed and tailored based on personal experience, are more suitable for VSEs [32]. These lightweight methods are inductive (bottom-up), focused on the most critical segments of the practice, and facilitate organizational learning within organizations that implement them [37]. According to Pettersson et al [38], light weight software process assessment and improvement should be based on the organization's experience and knowledge, and supported by triangulation of data (use of multiple data sources).…”
Section: Software Maintenancementioning
confidence: 99%
“…Kao segment tog projekta je realizovan podprojekat sistematizacije znanja koje se odnosi na proces održavanja softvera. Segmenti ovog istraživanja su delimično publikovani, a obuhvataju opis pristupa identifikaciji znanja u postupku procene procesa [18], diskusiju o primeni kvalitativnih metoda koje čine suštinu postupka identifikacije i sistematizacije znanja [22], prikaz induktivnih metoda u procenjivanju procesa koje su esencijalne za identifikovanje znanja o procesima [23], prikaz segmenta tematskog okvira sa znanjem o procesiranju zahteva za održavanjem softvera [24], i prikaz koncepta povratnih informacija (feedback) u procenjivanju softverskih procesa i identifikovanju znanja [25].…”
Section: Iskustva Iz Prakseunclassified
“…1). Organizaciono učenje i podrška za identifikaciju i sistematizaciju znanja (aktivnosti u okviru upravljanja znanjem) su omogućene primenom induktivnog pristupa u procenjivanju softverskih procesa [23], što je zapravo pristup odozdo-na-gore (bottom-up) i samim tim omogućuje identifikaciju znanja koje postoji u organizaciji (u glavama zaposlenih). Osnovne karakteristike ovog pristupa su:…”
Section: A Identifikacije I Sistematizacije Znanja U Malom Softverskunclassified